Burden of arrhythmias in peripartum cardiomyopathy: Analysis of 9841 hospitalizations. (15th May 2017) - Mallikethi-Reddy, Sagar; Akintoye, Emmanuel; Trehan, Naveen; Sharma, Shikha; Briasoulis, Alexandros; Jagadeesh, Kavyashri; Rubenfire, Melvyn; Grines, Cindy L.; Afonso, Luis
Abstract: Background: Peripartum cardiomyopathy (PPCM) is associated with significant morbidity and mortality. Arrhythmogenic causes of death have been implicated in a significant number of patients. However, there is a dearth of systematic studies evaluating the burden of arrhythmias in PPCM. Methods: We used the Healthcare Utilization Project, Nationwide Inpatient Sample database (2007–2012) and identified 9841 hospitalizations for women aged ≥ 18 years with a primary diagnosis of PPCM. Frequency of arrhythmias, utilization of electrophysiologic procedures, length of stay, hospitalization costs and outcomes associated with arrhythmias were determined. Results: Mean age was 30.05 ± 6.69 years. Arrhythmias were present in 18.7% of hospitalized PPCM cohort. Ventricular tachycardia was the most common arrhythmia and was noted in 4.2%. Approximately 2.2% of cases experienced cardiac arrest. Electrical cardioversion was performed in 0.3%, Catheter ablation in 1.9%, PPM implantation in 3.4% and ICD in 6.8% of hospitalizations for PPCM with arrhythmias. In-hospital mortality was 3-times more frequent in arrhythmia cohort (2.1% vs. 0.7%). Hospitalization costs were significantly higher in PPCM with arrhythmias. Elixhauser comorbidity score (adjusted OR:1.10; 95%CI:1.02–1.18; p = 0.016), in-hospital mortality (adjusted OR:2.35; 95%CI:1.38–4.02; p = 0.002), cardiogenic shock (adjusted OR:2.61; 95%CI:1.44–4.72; p = 0.002), utilization of balloon pump (adjusted OR:13.4; 95%CI: 2.55–70.53; p < 0.001), Swan-Ganz catheterization (adjusted OR:3.12; 95%CI:1.21–8.06; p = 0.019), and coronary angiography (adjusted OR:1.79; 95%CI:1.19–2.70; p = 0.005) were significantly associated with arrhythmias in PPCM. Conclusions: Arrhythmias were present in 18.7% of PPCM related hospitalizations. Morbidity, in-hospital mortality, length of inpatient stay, hospitalization costs and cardiac procedure utilization were significantly higher in the arrhythmia cohort.